Social determinants of mental health among Filipino college students Elli Rose L. Elola and Hannah R. Manero. - Elola, Elli Rose L.
The present study focuses on assessing the social determinants of mental health (i.e., family functioning, academic performance, socio-economic status, access to mental health care services, mental health literacy, and quality of neighborhood) and the mental health profile of Filipino college students using a cross-sectional correlational research design. Two hundred thirty five participants from five universities in Western Visayas took part in this study. Spearman's Rho and Multiple Linear Regression Analysis were used to determine the correlation between variables as well as identify the social determinants of mental health. Results showed that variables such as family functioning, academic performance, access to mental health care services, and quality of neighborhood significantly correlate with mental health. However, when analyzed using multiple linear regression, only family functioning, access to mental health care services, and quality of neighborhood predicts Filipino college students' mental health. This study adds to the corpus of evidence which identifies predicting factors of Filipino college students' mental health outcomes. The results of this study will provide data which could assist decision makers in developing evidence-informed interventions. Keywords: social determinants of mental health, mental health